PENGARUH KEMANDIRIAN BELAJAR MATEMATIK SISWA TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMA - Agil Maulana Akhdiyat; Wahyu Hidayat (IKIP Siliwangi, 2018)
This research aims to analyze and in study about influence of mathematical by self regulated learning against the ability of mathematical creative thinking high school students. The methods used in this research is quantitative data with the correlational method. The population in this research is a high school student in the city of Bandung with sampels as many as 31 student that assigned by techniques purposif sampling at one high school in the city of Bandung. The instruments in this research is a test of the ability of mathematical creative thinking as much as 4 items and scale self regulated learning as much as 10 scale statements. Then the results of this study that the ability of mathematical creative thinking high school students influenced positively by the mathematical self regulated learning equal to 87.5%, 12.5% influenced by factors other than the independent of self regulated learning mathematics students.